Monetary policy and central banking in India - Mutalik Desai, V. R.; Ghonasgi, B. D. (Bombay : Popular Prakashan, 1969)
Monetary policy plays a crucial role in shaping the economic destiny of a nation, for money and credit influence vitally the course, nature and volume of economic activities. This book is a cooperative endeavor of the specialists in the subject of banking and monetary policy. The scope is limited to the study of the central banking and monetary policy in India.
Bibliography: p. 179-180.
usc 18/07/17
Loans
Keywords: Monetary policy; Banks and banking, Central; India